Effects of storage environment on the moisture content and microbial growth of food waste. (15th May 2018) - Chen, Ying-Chu; Hsu, Yi-Cheng; Wang, Chung-Ting
Abstract: Food waste (FW) has become a critical issue in sustainable development as the world's population has increased. Direct incineration of FW remains the primary treatment option. The moisture content of FW may affect the energy efficiency of incineration. In Taiwan, FW, which includes raw (r-FW) and post-consumer (p-FW) waste, is often stored in freezers before pretreatment. This study evaluated the effects of storage environment on the moisture content and microbial growth of FW. Storage at 263 K was associated with the largest reduction in moisture content in both r-FW and p-FW. At 263 K, the moisture content of r-FW and p-FW was lowest at 96 and 72 h, respectively. The E.coli and total bacteria counts were steady over 120 h when stored at 263 K. Storage at 253 K required the greatest electricity consumption, followed by 263 K and 258 K. Based on the reduction of moisture content and increase in energy efficiency, it is suggested that FW is placed in temporary storage at 263 K before (pre)treatment. The results of this study will help waste-to-energy plants, incinerators, and waste management enterprises to implement proper (pre)treatment of FW for sustainable waste management. Highlights: The effects of storage environment on the moisture content of food waste were evaluated. FW is stored for at least 72 h at 263 K to obtain the largest reduction in moisture content. The E.coli and total bacteria counts were steady over 120 h when stored at 263 K. Storage at 253 K required the greatest electricity consumption, followed by 263 K and 258 K.